Bronze Age metal circulation in China – ERRATUM. (8th August 2017) - Pollard, A.M.; Bray, P.; Hommel, P.; Hsu, Y.-K.; Liu, R.; Rawson, J.
Abstract : In the article by Pollard et al. (2017 ), Figure 2 was incorrectly duplicated asFigure 5 .